Otoritas Kitab Kuning Dalam Putusan Hakim: Analisis Putusan Hakim di Mahkamah Syar’iyah Lhokseumawe Aceh - Safriadi, Safriadi (Analisis: Jurnal Studi Keislaman, 2019)
In the Islamic law (Fiqh) tradition, "Kitab Kuning" is one of reference in establishing the law. In this context, Kitab Kuning should have the authority to establish law in judicial institutions that implement the Shari'ah system, as is the Syari'ah Court of Lhokseumawe, Aceh. However, the facts show that the judges at the Syar'iyah Court of Lhokseumawe Aceh only referred to legislation as a reference in deciding cases. This article will discuss how the pattern of judges' decision-making and how the position of the Kitab Kuning in making decisions at the Syar'iyah Court of Lhokseumawe? This research is field research and classified as qualitative with a normative juridical approach and empirical sociological approach. This study found that the judge collects various facts that have been submitted by the plaintiff and the defendant, then holds a deliberation to terminate the case to purge general matters to be specific. The Kitab Kuning authority in making decisions at the Mahkamah Syar'iyah of Lhokseumawe is in a position parallel to al-quran and hadith, as a material source. because the source of the decisions of the judges at the Syar'iyah Court of Lhokseumawe came from the PA Act of 1974, the presidential instruction in 1991, and the judicial law in 1970 (formal sources). However, the 3 sources of law in each decision are inspired by the legal descriptions of Kitab Kuning through the Kompilasi Hukum Islam (KHI). Thus the judges should no longer refer to the Kitab Kuning when deciding the case. Because the formal and material laws that apply in the Religious Courts are available and have permanent legal force and the requirements proclaimed by the government are worthy of review.